The Role of Vocabulary Knowledge In Improving Listening Accuracy - Sari, Feby Wulan; Lubis, Angga Dinata; Rambe, Putri Auliasyah; Siregar, Indah; Siregar, Deasy Yunita (PT. Kreasi Karya Majakata, 2026)
Vocabulary knowledge has long been recognized as a crucial component of language proficiency. In the context of listening skills, vocabulary plays a significant role in enabling learners to recognize spoken words, interpret meaning, and accurately comprehend oral input. This journal article aims to examine the role of vocabulary knowledge in improving listening accuracy among language learners. Using a comprehensive review of relevant theories, empirical studies, and pedagogical perspectives, this paper discusses how vocabulary size, depth of vocabulary knowledge, and lexical processing influence listening comprehension accuracy. The discussion also highlights implications for language teaching and learning, particularly in English as a Foreign Language (EFL) contexts. The findings suggest that strengthening learners’ vocabulary knowledge significantly enhances their listening accuracy and overall communicative competence.